Work of mathematics teacher educators : exchanging ideas for effective practice - Watanabe, Tad, 1959-; Thompson, Denisse R. 1954- (Emerald Publishing Limited, 2014)
(Orginally published in 2004)A major focus of teacher education is the development of preservice teachers. However, it should not be the only focus of those who work in teacher education. Educating inservice teachers in equally important, and the conversation among those involved in mathematics teacher education needs to include discussion of this group as well. This conversation also highlights a need for professional development for teacher educators and research on the development of teacher educators. This monograph discusses issues in educating all of these groups of individuals in an effort to continue the conversation among those involved in mathematics teacher education.
Includes index.
Keywords: Mathematics -- Study and teaching -- United States.; Mathematics teachers -- Training of -- United States.; Education -- Teaching -- Subjects -- Mathematics.; Teaching of a specific subject.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books